Public Services Based on Health Protocols During the Covid-19 Pandemic in Bontang Lestari Village: Pelayanan Publik berdasarkan Protokol Kesehatan Pada Masa Pandemi Covid-19 Di Kelurahan Bontang Lestari - Salam, Indriati; Zainal Arifin, Muhammad; Helminasari, Shorea (Wadah Inovasi Indonesia, 2023)
Public service providers must react to the COVID-19 pandemic. Many government regulations to prevent this virus's spread affect service providers' public service standards. Improving public service standards will help stop this infection. Researchers in Bontang Lestari Village, hit by the COVID-19 epidemic, observed issues, including limited service hours, unprepared health protocol facilities, and uneven health protocol socialization. Then the research question is how public services based on health protocols are implemented during the COVID-19 pandemic in Bontang Lestari Village and what are the obstacles. This study examines public service health procedures during the COVID-19 pandemic in Bontang Lestari Village and the challenges they faced. This study used qualitative research. According to the research, the health protocol for using masks has not been optimally implemented because residents/employees still take off their masks when chatting/conducting services, the health protocol for washing hands has gone well and in accordance with the rules applied, and the health protocol for maintaining distance between residents has been set at 1 meter. Residents and staff' ignorance of health protocols hinders the public service process based on them. Thus, the chance of getting COVID-19 is rising, and residents have less time to take care of their requirements, making services seem substandar.